THE APPLICATION OF E-NOKEN AS A DIGITAL LITERACY MEDIA IN IMPROVING LANGUANGE ABILITY AND STRENGTHENING CHARACTER IN STUDENTS AT SMA OIKUMENE KOTA SORONG - Gaspersz, Sherly; Matahelumual, Fretty (Journal International of Lingua and Technology, 2025)
This study aims to examine the effectiveness of implementing e-Noken, a digital literacy medium based on local Papuan culture, in improving the language ability and character building of students at SMA Oikumene Kota Sorong. The study used a pre experimental one group pretest posttest design with a mixed methods approach, involving 32 students as participants through purposive sampling. The research instruments included language ability tests, character strengthening questionnaires, participatory observation, and semi-structured interviews. Quantitative analysis results showed a significant increase in language ability, with an average pre-test score of 38.44 and a post-test score of 77.66, as well as a gain of 0.7658 (high category). Questionnaire analysis showed participants’ positive perceptions of the implementation of e-Noken, both in terms of ease of use and its impact on character building. The interview results reinforced these findings, showing that e-Noken encourages discipline, responsibility, and appreciation for local culture. Although the direct correlation between the implementation of e-Noken and the variables of language ability and character building was not significant, there was a very strong relationship between language ability and character building (r = 0.930, p < 0.01). This study confirms that the integration of local culture-based digital literacy media has a dual impact: it improves academic ability while instilling character values, in line with 21st-century educational goals and learning principles.